2009
DOI: 10.1560/ijee.55.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Facial expressions in various emotional states in congenitally blind and sighted subjects

Abstract: Most of the studies comparing facial expressions of born blind and sighted persons that have been carried out up until now have involved children as subjects. Various studies claimed that the quantity and quality of facial expressions of congenitally blind persons deteriorate with increasing age. Here, we compared facial expressions of born blind and sighted individuals using adults predominantly. Facial expressions were documented in an individual interview inducing such emotions as think-concentrate, sadness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…This link between an emotion and a particular facial expression is expected to be innate and largely independent of culture. The finding that congenitally blind children and adults can produce voluntary facial expressions of different basic emotions such as joy, anger, or sadness supports the idea of innateness [ 5 7 ]. On the other hand, empirical studies provide inconsistent evidence for the claim of cultural influences on facial expressions (for a recent review, see [ 8 , 9 ]), but it seems that social contexts affect facial expressions and their recognition.…”
Section: Introductionmentioning
confidence: 75%
“…This link between an emotion and a particular facial expression is expected to be innate and largely independent of culture. The finding that congenitally blind children and adults can produce voluntary facial expressions of different basic emotions such as joy, anger, or sadness supports the idea of innateness [ 5 7 ]. On the other hand, empirical studies provide inconsistent evidence for the claim of cultural influences on facial expressions (for a recent review, see [ 8 , 9 ]), but it seems that social contexts affect facial expressions and their recognition.…”
Section: Introductionmentioning
confidence: 75%
“…However, the subjects were much older (see Table 2) than two to six months, which is the age at which typical children start expressing facial emotions. An exception is the emotion "anger", for which Peleg et al (2009) found a less clear display in subjects with blindness than in subjects with sight. An exception is the emotion "anger", for which Peleg et al (2009) found a less clear display in subjects with blindness than in subjects with sight.…”
Section: Outcomes Of Intersubjectivity Measuresmentioning
confidence: 98%
“…Four other studies involving children with blindness (Galati, Miceli, & Sini, 2001;Galati, Sini, Schmidt, & Tinti, 2003;Peleg et al, 2009;Roch-Levecq, 2006) measured variables relevant to primary intersubjectivity by analysing facial expressions of emotions. However, the subjects were much older (see Table 2) than two to six months, which is the age at which typical children start expressing facial emotions.…”
Section: Outcomes Of Intersubjectivity Measuresmentioning
confidence: 99%
“…Osnovni zaključak je da se kod osoba koje su slepe od rođenja sa starenjem smanjuje intenzitet facijalne ekspresije (Peleg et al, 2009). …”
Section: Uvodunclassified